Cardiogenic Shock due to Psychosis-Induced Inverted Takotsubo Cardiomyopathy Bridged-to-Recovery with a Percutaneous Left Ventricular Assist Device - Ravi Korabathina; Warren Abel; Arthur Labovitz (Case Reports in Cardiology)
Inverted Takotsubo cardiomyopathy, a less common variant in the spectrum of stress-induced cardiomyopathy, is increasingly being reported. This report describes an acute psychiatric illness leading to the onset of this syndrome. The patient presented here developed cardiogenic shock but successfully recovered with the use of a percutaneous left ventricular assist device.